P25 Standards of end-of-life care in patients with non-malignant respiratory disease. (12th November 2015) - Brothers, H; Gleeson, A; Kilbane, J; Scott, M; Evans, J; Powell, E; Margetts, S
Abstract : Objectives: Recognising the end of life phase in chronic non-malignant lung conditions remains a challenge which has been proposed as a major barrier to ensuring effective end-of-life care in this population. 1 Our aims were threefold. Firstly, to establish whether patients who died of causes related to their lung condition could have been predicted to have been in the last 6–12 months of their lives. Secondly, to evaluate the standard of care they received leading up to their death. Finally, to compare end-of-life care received by patients with chronic obstructive pulmonary disease (COPD) and interstitial lung disease (ILD). Methods: A retrospective review of deaths due to COPD and ILD over a 26 month period in two acute hospitals in South Wales using paper and electronic health records. Gold Standards Framework (GSF) prognostic indicators of poor prognosis were identified, and 'standards of care' evaluated in the 12 months preceding death. Results: 119 cases were analysed. 83% of patients could have been identified as 'approaching end of life' (AEOL) using GSF criteria. 'Standards of care' were variably met: do not attempt cardiopulmonary resuscitation (DNACPR) forms were completed in 93% of cases. Advanced care planning, establishing preferred place of care and use of specific end-of-life care documentation took place in <1%, 7% and 14% respectively. COPD patients had more indicators of poor prognosis than patients with ILD but received fewer 'standards of care'. Conclusions: The majority of patients in our study could have been identified as AEOL and therefore ought to have been in receipt of the 'standards of care'. There is a need to improve recognition of patients that are AEOL in order that they receive better end-of -life care. Further investigation to confirm or refute the discrepancy in care between COPD and ILD patients is necessary. Research into the best means of identifying, and subsequent provision of care, for patients with non-malignant respiratory disease is also required. Reference: 1 Boland J, Martin J, Wells A, Ross J. Palliative care for people with non-malignant lung disease: summary of current evidence and future direction. Palliat Med . 2013;27 (9):811–816